Comparative study of EMI shielding effectiveness for carbon fiber pultruded polypropylene/poly(lactic acid)/multiwall CNT composites prepared by injection molding versus screw extrusion. Issue 34 (8th May 2017) - Lee, Seung Hwan; Lee, Yeongbeom; Jang, Myung Geun; Han, Chonghun; Kim, Woo Nyon
ABSTRACT: The electrical conductivity and electromagnetic interference (EMI) shielding effectiveness of the composites of polypropylene/poly(lactic acid) (PP/PLA) (70/30, wt %) with single filler of multiwall carbon nanotube (CNT) or hybrid fillers of nickel‐coated carbon fiber (CF) and CNT were investigated. For the single filler composite, higher electrical conductivity was observed when the PP‐ g ‐maleic anhydride was added as a compatibilizer between the PP and PLA. For the composite of the PP/PLA (70/30)/CF (20 phr)/CNT (5 phr), the composite prepared by injection molding observed a higher EMI shielding effectiveness of 50.5 dB than the composite prepared by screw extrusion (32.3 dB), demonstrating an EMI shielding effectiveness increase of 49.8%. The higher values in EMI shielding effectiveness and electrical conductivity of the PP/PLA/CF (20 phr)/CNT (5 phr) composite seemed mainly because of the increased CF length when the composites were prepared using injection molding machine, compared with the composites prepared by screw extrusion. This result suggests that the fiber length of the conductive filler is an important factor in obtaining higher values of electrical conductivity and EMI shielding effectiveness of the PP/PLA/CF/CNT composites. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45222. Abstract :